Du dévoiement de l'Histoire au génocide. L'Allemagne nazie et la préparation de la Seconde Guerre mondiale (années 1920-1930) - Barton, Deborah (Quand l'Histoire sert à faire la guerre, 2023)

Épilogue: L'Histoire peut-elle servir la paix? - Bouchard, Carl (Quand l'Histoire sert à faire la guerre, 2023)

« Ehrliche Kriegsleute » : la construction de la représentation du lansquenet au royaume de France lors de la Renaissance (1486-1559) - Handfield, Nicolas (Université de Montréal, 2019)
Through an approach that seeks to link the question of the culture of war to the awareness of the social, economic and political dimensions of war, this study highlights the construction of the figure of the landsknecht through the prism of the practices of these German mercenaries and the representations of French contemporaries. To identify this dominant figure of the Renaissance, it is a question of circumscribing the strategies implemented by the lansquenets, i.e. the arsenal of symbols, speeches and behaviours to which the members of this group refer, and to confront them with the discourses of the French military and civilians in order to apprehend the perception they have of the landsknechte and the behaviours they develop towards them. The dialectic between the practices of the Lansquenets and the French representations of them illustrate the profound transformations of the French monarchy at the dawn of the Modern Era and reveals a society's apprehension of alterity.
Keywords: Culture; Foreigner; History - Military / Histoire - Militaire (UMI : 0722); Identity; Identité; Landsknecht; Lansquenet; Mercenaire; Mercenary; Monarchie; Monarchy; Representation; Représentation; Violence; Étranger

« Au service d’un autre roi » : les troupes étrangères allemandes au service du royaume de France (1740-1763) - Portelance, Philipp (Université de Montréal, 2019)
The memory of the French Revolution often refers to the victory of the Nation. The Revolution created the nation state, but also the standing army of citizen-soldiers, thus rejecting mercenary enterprise and the use of foreign troops. However, the reality is quite different, since the armies of the Revolution and of the many French Republic all had foreign contingents, the most famous being the French Foreign Legion. Even today, the use of private enterprise in warfare is again booming. During the warring period from 1740 to 1763, which saw two great European wars —the Austrian Succession (1740-1748) and the Seven Years (1756-1763) wars—become world wars, the use of foreign troops increased in the kingdom of France. It was not solely the case in the armies of the Rois Très-Chrétiens: foreigners served in all European armies, notably in those of England, Spain, Prussia, Austria and Russia. They were not only used to inflate the ranks of the armies, but also to seek expertise in military knowledge. In the middle of the 18th century, the Prussian model was in fashion and was introduced to France by the German standing foreign regiments. This phenomenon has been neglected by the literature and by the military history (except regarding Swiss and Irish troops). This research seeks to fill this gap. Using social and cultural history, as well as the history of representations, it aims at understanding who these foreign soldiers were, where they came from, and what were their motivations to serve for France. Ultimately, this thesis examines the German and the French military cultures in the 18th century and highlights the role of German foreign regiments in cultural and warfare transfers.
Keywords: Allemagne; Ancien régime; Cultures de guerre; Foreign troops; France; Germany; Guerre de Sept ans (1756-1763); Guerre de succession d'Autriche (1740-1748); Histoire militaire; History - Military / Histoire - Militaire (UMI : 0722); Military cultures; Military history; Old regime; Prusse; Prussia; Representation; Représentations; Seven year's war (1756-1763); Troupes étrangères; War of the Austrian succession (1740-1748)